2021
DOI: 10.3390/ijms221910472
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Protective Properties of a Xyloglucan-Based Nasal Spray in a Mouse Model of Allergic Rhinitis

Abstract: A breached nasal epithelial barrier plays an important role in driving allergic rhinitis (AR). Corticosteroids remain the standard of care (SoC) but come with side effects, thus alternative safe and effective treatments able to avoid inflammation and restore barrier integrity are needed. The aim of the present study is to evaluate the barrier-forming capacity of a xyloglucan-based nasal spray (XG) and compare its efficacy to several SoC treatments (corticosteroid spray, oral mast-cell stabilizer and oral antih… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…ELISA kits were used to detect the levels of IL-5 (#BMS610), IL-13 (#BMS6015), IL-9 (#88-8092), IL-4 (#BMS613), GSH (#MBS266871), CAT (#MBS160589), SOD (#MBS034842), caspase-3 (#MBS849298-100), caspase-9 (#LS-F21324), and caspase-8 (#LS-F32785) in serum or colon tissues of mice as previously described [ 32 , 33 ], and according to the manufacturer’s protocols.…”
Section: Methodsmentioning
confidence: 99%
“…ELISA kits were used to detect the levels of IL-5 (#BMS610), IL-13 (#BMS6015), IL-9 (#88-8092), IL-4 (#BMS613), GSH (#MBS266871), CAT (#MBS160589), SOD (#MBS034842), caspase-3 (#MBS849298-100), caspase-9 (#LS-F21324), and caspase-8 (#LS-F32785) in serum or colon tissues of mice as previously described [ 32 , 33 ], and according to the manufacturer’s protocols.…”
Section: Methodsmentioning
confidence: 99%
“…β-actin mRNA was used as an endogenous sham to allow for the relative quantification. RT-qPCR was made for the evaluation of Mucin 5 AC (MUC5AC) gene expression (5 0 CCAGCACCATCTCTACAACCC 3 0 and 3 0 GCAAAGCTCCTGTTTGCACTC 5 0 ) using Power Up Sybr Master Mix (Applied Biosystems, Carlsbad, CA, USA) and a QuantStudio 6 Flex Real-Time PCR System (Applied Biosystems, Carlsbad, CA, USA) (Lanza et al, 2021). The amplified PCR products were quantified by measuring the calculated cycle thresholds (CT) of target genes and β-actin mRNA.…”
Section: Evaluations On Laryngopharyngeal Refluxmentioning
confidence: 99%
“…40,130,131 Major protease components derived from HDM, such as Der p 1, have been demonstrated to directly disrupt the integrity of ZO-1, occludin, JAM-A, and claudin-1 in order to facilitate nasal epithelial leakage. [132][133][134] Moreover, both HDM 72,73,82,135 and ovalbumin (OVA) [136][137][138][139][140][141] were found to disrupt the nasal epithelial barrier function ex vivo. Regarding plant allergens, Fukuoka et al 142 suggested that Japanese cedar and ragweed could reduce ZO-1 expression and increase permeability through the Cystatin SN pathway in RPMI2650 cells and BALB/c mice.…”
Section: Allergensmentioning
confidence: 99%
“…73,82 Additionally, Budesonide also alleviated nasal epithelial barrier dysfunction induced by TNF, 168 PM 2.5 , 144 and OVA. 138 Although it remains unclear whether dexamethasone (Dex) can effectively alleviate symptoms in CRS, there is evidence suggesting that Dex can reverse the impairment of TJs in IL-13-induced primary HNECs 93 and PM 10 -induced RPMI2650 cells. 146,147 Meanwhile, oral administration 136 and nasal aerosol inhalation 146,147 while preventing ZO-1 degradation in the nasal epithelium of OVAinduced AR mice.…”
Section: Response To Medical Treatmentsmentioning
confidence: 99%